2014
DOI: 10.1002/adsc.201400767
|View full text |Cite
|
Sign up to set email alerts
|

Alkynylboranes: A Practical Approach by Zinc‐Catalyzed Dehydrogenative Coupling of Terminal Alkynes with 1,8‐Naphthalenediaminatoborane

Abstract: Under zinc Lewis acid catalysis, terminal alkynes coupled dehydrogenatively with 1,8‐naphthalenediaminatoborane [HB(dan)]. It is important to note that the resulting alkynylboranes with an C(sp)B(dan) bond are isolable by column chromatography on silica gel (SiO2) and are usable as coupling partners for palladium‐ and copper‐catalyzed cross‐coupling reactions with (hetero)aryl halides.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 103 publications
1
56
0
Order By: Relevance
“…Indeed, event though many reports followed pioneering works by Smith, Hartwig on C−H borylation, these methods are limited to C(sp 2 )−H and C(sp 3 )−H activation, and only a few reported C(sp)−H dehydrocoupling. In addition to Ozerov's seminal paper, it has been shown that dehydrocoupling can be catalyzed by Zn(OTf) 2 , NHC‐Zn (NHC: N‐heterocyclic carbene), (CAAC)CuX (CAAC: cyclic (alkyl)(amino)carbene) or Fe(OTf) 2 ; the borylating agent being pinacolborane (HBpin) or 1,8‐diaminonaphthalenylborane (HBdan).…”
Section: Methodssupporting
confidence: 93%
“…Indeed, event though many reports followed pioneering works by Smith, Hartwig on C−H borylation, these methods are limited to C(sp 2 )−H and C(sp 3 )−H activation, and only a few reported C(sp)−H dehydrocoupling. In addition to Ozerov's seminal paper, it has been shown that dehydrocoupling can be catalyzed by Zn(OTf) 2 , NHC‐Zn (NHC: N‐heterocyclic carbene), (CAAC)CuX (CAAC: cyclic (alkyl)(amino)carbene) or Fe(OTf) 2 ; the borylating agent being pinacolborane (HBpin) or 1,8‐diaminonaphthalenylborane (HBdan).…”
Section: Methodssupporting
confidence: 93%
“…On the other hand, Tsuchimoto et al. reported in the dehydrogenative borylation reaction that the Zn(OTf) 2 can activate the B−H bond, which initiates the evaluation of H 2 gas upon reaction with phenylacetylene . Based on this preceding study, we monitored the stoichiometric reaction of 1 a with in situ generated active species A in a sealed system by 1 H NMR spectroscopy; we did not observe any production of H 2 , which suggests that the deprotonation mechanism is not operated under our reaction conditions.…”
Section: Methodsmentioning
confidence: 99%
“…More recently,p ioneering research concerningt he zinc-catalysed borylation reactions of alkyl halides, [11a] aryl halide, [11b] and dual CÀXa nd CÀHb orylation of aryl halides, [11c] have been reported by Mardera nd coworkers. Further,t he dehydrogenative borylation of terminal alkynes with HBdan [12] (dan = 1,8-diaminonapthalene) and the borylation of aryl diazonium salt and aryltriazene with B 2 pin 2 [13] was achieved using Zn(OTf) 2 and Zn(ClO 4 ) 2 as catalysts, respectively.A lso, Aldridge and co-workers developedapalladiumcatalysed borylation of aryl halides and acyl chlorides using air stable zincboryl reagent. [14] NacnacZn-H (Nacnac = N,N'-bis-2,6diisopropylphenyldiketiminate) catalysed hydrosilylationa nd hydroboration of N-heterocycles has been recently reported by Nikonov et al (Scheme 1c).…”
mentioning
confidence: 99%
“…Uchiyama and co‐workers developed an interesting and general borylzincate‐complex‐mediated procedure for the borylation of aryl halides and borylzincation of benzynes/terminal alkynes . A zinc catalyst has also been applied in the dehydrogenative coupling of terminal alkynes with 1,8‐naphthalenediaminatoborane . Alkynylboranes were produced in good yields.…”
Section: Zn‐catalyzed Borylation: Screening Of Reaction Conditions[a]mentioning
confidence: 99%